PERUBAHAN PENUTUPAN LAHAN DI DAS TABUNIO, KABUPATEN TANAH LAUT, KALIMANTAN SELATAN - Dwi Tratna Wibawa; Abdi Fithria; Khairun Nisa (Universitas Lambung Mangkurat, 2021)
The objectives of this study are (1) analyzing the land cover class, (2) analyzing the changes of land cover area in Tabunio Watershed from 2000 to 2018 and (3) analyzing the land cover of Tabunio Watershed in 2018 which is included in the forest area. The data used are watershed boundary spatial data from the Ministry of Environment and Forestry Directorate of PDAS-HL, spatial data of land cover resulting from interpretation of landsat images from the Directorate of IPSDH Directorate General of Planning and Environmental Planning in 2000, 2003, 2006, 2009, 2012, 2015 and 2018 and spatial data on forest areas from the Ministry of Forestry. Classification of land cover class by the modification method from 23 classes to 11 classes namely Forest, Plantation Forest, Open Land, Mangrove, Plantation, Settlement, Dry Land Agriculture, Rice Fields, Shrubs, Pond and Water Bodies. Data processing through geographic information systems (GIS) software ArcGis 10 and Exel. This research method uses overlapping and descriptive analysis. Land Cover Conformity Test Results an accuracy rate of 91%. The results of the analysis of land cover change show that the plantation land cover class experienced the greatest rate of change during the period of 2000-2018 which increased by an area of 10.791,70 hectares (2.169,16%). The results of the analysis land cover of Tabunio Watershed in 2018 which is included in the forest area show that Dryland Agriculture covering 4.091.48 hectares (36.31%) is the largest land cover class found in all forest area functions.Keywords: Watershed; GIS; Land Closing Classes; Suitability of Land Closure; Change in Land Closure; Forest Area